PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Hasbiya Miftahul Jannah; Linda Zakiah; Petrus Paulus Mbette Suhendro (STKIP Subang, 2025)
In the 21st century, learning is still dominated by teachers as a source of learning, so that students only get knowledge from teachers. If learning activities only come from teachers, students are not used to linking lesson materials with problems that occur in everyday life, and this causes them to lose critical thinking skills. Thus, teachers must choose the right learning model to train critical thinking skills. One learning model that can be used to improve students' critical thinking skills is the Problem Based Learning (PBL) learning model. The purpose of this study was to determine the effect of the problem based learning model on critical thinking skills in the Pancasila Education subject of grade IV students. The research method used was quantitative research using the experimental method. The results of this study showed that the average posttest score of the experimental class was 80.60, while the average posttest score of the control class was 65.80. The results of the t-test hypothesis test obtained the results of the analysis that the Sig. (2-Tailed) value was 0.001 <0.05. It can be concluded that the null hypothesis Ho is rejected and Ha is accepted, meaning that there is a difference in students' critical thinking in Pancasila Education learning between the experimental class and the control class. With the difference in learning models used, it is proven that the Problem Based Learning learning model has a significant influence on critical thinking in Pancasila Education of grade IV students.